The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fonc.2021.652831
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism of the c-Myc/NEAT1 Axis Mediating Colorectal Cancer Cell Response to Photodynamic Therapy Treatment

Abstract: Photodynamic therapy (PDT) is considered a potential treatment regimen for colorectal cancer cases (CRC). p53 signaling and the miR-124/iASPP axis play an essential role in the PDT resistance of CRC cells. PDT treatment downregulated NEAT1 expression in p53wt HCT116 and RKO cells. In these two cell lines, NEAT1 silencing enhanced the suppressive effects of PDT on cell viability and apoptosis. Within the subcutaneously implanted tumor model, NEAT1 silencing enhanced PDT-induced suppression on tumor growth. Rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…One of the biggest obstacles to treating colorectal cancer is the lack of a molecular biomarker. Studies have shown that NEAT1 expression is upregulated in colorectal cancer tissues, and a higher level of NEAT1 contributes to the poor overall survival and disease-free survival [ 44 , 45 ]. Moreover, NEAT1 can also promote the proliferation and metastasis of colorectal cancer in vivo and in vitro [ 44 , 45 ].…”
Section: Neat1 Sponges Micrornas and Stabilizes Mrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the biggest obstacles to treating colorectal cancer is the lack of a molecular biomarker. Studies have shown that NEAT1 expression is upregulated in colorectal cancer tissues, and a higher level of NEAT1 contributes to the poor overall survival and disease-free survival [ 44 , 45 ]. Moreover, NEAT1 can also promote the proliferation and metastasis of colorectal cancer in vivo and in vitro [ 44 , 45 ].…”
Section: Neat1 Sponges Micrornas and Stabilizes Mrnasmentioning
confidence: 99%
“…Studies have shown that NEAT1 expression is upregulated in colorectal cancer tissues, and a higher level of NEAT1 contributes to the poor overall survival and disease-free survival [ 44 , 45 ]. Moreover, NEAT1 can also promote the proliferation and metastasis of colorectal cancer in vivo and in vitro [ 44 , 45 ]. NEAT1 can elevate the expression of some growth factors and transcription factors such as IGF2, GDNF, and BACH1, which facilitate the progression of colorectal cancer [ 44 , 46 , 47 ].…”
Section: Neat1 Sponges Micrornas and Stabilizes Mrnasmentioning
confidence: 99%
“…Given the role of NEAT1 in cancer, several studies have been trying to unravel the molecular mechanisms regulating its expression and its targets. Recently, a study by Liu et al reported that NEAT1 is transcriptionally regulated by MYC, inducing its transcription [ 55 ]. Interestingly, a study by Zhu et al demonstrated that NEAT1 regulates chromatin remodeling through increasing acetylation levels at MYC promoter, inducing its expression, in colorectal cancer [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…NEAT1 knockdown facilitated the sensitivity of CRC cells to PDT and suppressed the effect of PDT on CRC growth through sponging miR-124It has been demonstrated that the p53 deletion or mutation can induce CRC cells resistance to PDT. The c-Myc/miR-124/NEAT1/p53/iASPP axis exerted their regulatory role in CRC response to the chemotherapy [ 111 ]. It was revealed that cleavage of gasdermin E (GSDME) as a member of the gasdermin family altered apoptosis to pyroptosis as a lytic cell death which is correlated with chemotherapy along with anticancer immunity in CRC [ 112 115 ].…”
Section: Clinical Significance Of Neat1mentioning
confidence: 99%